Critical Period for Palmer Amaranth (Amaranthus palmeri) Control in Pickling Cucumber. (October 2018) - McGowen, Samuel J.; Jennings, Katherine M.; Chaudhari, Sushila; Monks, David W.; Schultheis, Jonathan R.; Reberg-Horton, Chris
Abstract: Field studies were conducted in North Carolina to determine the critical period for Palmer amaranth control (CPPAC) in pickling cucumber. In removal treatments (REM), emerged Palmer amaranth were allowed to compete with cucumber for 14, 21, 28, or 35 d after sowing (DAS) in 2014 and 14, 21, 35, or 42 DAS in 2015, and cucumber was kept weed-free for the remainder of the season. In the establishment treatments (EST), cucumber was maintained free of Palmer amaranth by hand removal until 14, 21, 28, or 35 DAS in 2014 and until 14, 21, 35, or 42 DAS in 2015; after this, Palmer amaranth was allowed to establish and compete with the cucumber for the remainder of the season. The beginning and end of the CPPAC, based on 5% loss of marketable yield, was determined by fitting log-logistic and Gompertz equations to the relative yield data representing REM and EST, respectively. Season-long competition by Palmer amaranth reduced pickling cucumber yield by 45% to 98% and 88% to 98% during 2014 and 2015, respectively. When cucumber was planted on April 25, 2015, the CPPAC ranged from 570 to 1, 002 heat units (HU), which corresponded to 32 to 49 DAS. However, when cucumber planting was delayed 2 to 4 wk (May 7 and May 21, 2014 and May 4, 2015), the CPPAC lasted from 100 to 918 HU (7 to 44 DAS). This research suggested that planting pickling cucumber as early as possible during the season may help to reduce competition by Palmer amaranth and delay the beginning of the CPPAC.